Let's Talk Art: An interview with multidisciplinary artist Michelle Lisa Herman on collaborating with AI software to expose bias - McGavran, Sarah; Herman, Michelle Lisa (Culture Caleidoscoop, 2022)
What can artificial intelligence tell us about bias in art and technology? Art historian and museum editor Sarah McGavran’s interview with multidisciplinary artist Michelle Lisa Herman explores how Let’s Talk Art, a 2020 artist’s book written in collaboration with machine learning software, uses humour to reveal underrepresentation in both fields, particularly in terms of gender, disability, and race. Additional topics include exclusionary conceptions of art and artists, art speak versus accessible language, as well as objectivity and subjectivity.